Maternal plasma cell-free RNA as a predictive test for fetal lung maturation - Sean W. D. Carter; Kay Yi Michelle Seah; Si En Poh; Winston Koh; Haruo Usuda; Erin L. Johnson; Yusaku Kumagai; Tsukasa Takahashi; Lara J. Monteiro; Reyna Peñailillo; Gino Nardocci; Hannah R. S. Watson; et al. (BMC Medicine)
Abstract Background A lack of tests to assess fetal development impacts decision making around antenatal steroid use in women at risk of preterm birth. We analyzed the expression of 21 cfRNA targets related to human fetal lung maturation. Discovery studies were performed using maternal and fetal sheep plasma, with results compared to fetal lung mRNA expression. These findings were then validated in first, second, and third trimester human maternal plasma samples. Methods Discovery studies utilized a preterm sheep model of pregnancy. Date mated ewes received saline (control n = 6), or antenatal steroids (dexamethasone n = 12) (betamethasone n = 11) prior to delivery and ventilation. We analyzed the expression of 21 human cfRNA targets related to lung maturation in maternal and fetal sheep plasma and compared this to mRNA expression in fetal lung tissue. Findings were first validated in a separate cohort of sheep exposed to betamethasone (n = 8), intraamniotic LPS endotoxin for lung maturation (n = 6), or untreated term animals (n = 6). Findings were further validated in maternal plasma from a human cohort of uncomplicated term pregnancies (n = 10). Delivery and ventilation data were analyzed with ANOVA, Tukey HSD, and Dunnett T3 tests. A Random Forest algorithm identified genes that separated mature from immature fetal lung subgroups and determined AUC values for maternal and fetal cell-free RNA (cfRNA) feature sets to predict fetal lung maturation. Results We demonstrate that the analysis of 21 human cfRNA targets in maternal plasma is highly predictive of fetal lung maturation status across antenatal steroid induced (Dexamethasone AUC = 0.93; Betamethasone AUC = 1) and physiological (AUC = 1) lung development models. Maternal plasma cfRNA expression in the dexamethasone antenatal steroid group closely resembled direct fetal lung tissue mRNA expression. These findings were then validated in human maternal plasma samples (1st vs. 3rd trimester AUC = 0.96; 2nd vs. 3rd trimester AUC = 1). Conclusions Further development of this technology may provide a rapid, minimally invasive, and cost-effective clinical tool to optimize patient selection for initial and repeat courses of antenatal steroids, along with insights into the molecular mechanisms underlying fetal lung development. Graphical Abstract Graphical abstract illustrating the potential future application of maternal plasma cell-free RNA analysis. Created in https://BioRender.com .